Mapping of Re, a gene conferring the red leaf trait in ornamental kale (Brassica oleracea L. var. acephala). Issue 4 (25th June 2015) - Ren, Jie; Liu, Zhiyong; Niu, Ruiqing; Feng, Hui; Debener, T.
Abstract Variegated leaf colour is an important agronomic trait that affects the market value of ornamental kale (Brassica oleracea L. var. acephala). The red leaf phenotype in kale is due to anthocyanin accumulation. To investigate the pattern of inheritance of this trait, we constructed an F2 population by crossing 'Y005‐15', a double haploid with red leaves, with a white‐leaved double haploid, 'Y011‐13‐38', followed by self‐pollination. An F2 population consisting of 4284 individuals was used to study the inheritance of this trait, which showed that the character was controlled by a dominate gene. All of the 1050 white leaf trait plants in the F2 were used for mapping and developing markers linked to Re gene. Results showed that Re was mapped to a locus on linkage group C09 of Brassica oleracea, and the locus was mapped between six SSR markers (C9Z1, C9Z16‐1, C9Z90, C9Z94, C9Z96 and C9Z99), with a genetic distance of 6.7, 1.0, 0.3, 2.0, 2.1 and 0.4 cM from Re gene, respectively. These results may facilitate marker‐assisted selection of the red leaf trait in kale breeding as well as map‐based cloning of the red leaf trait gene.